Chosŏn-Centrism and Japan-Centrism in the Eighteenth Century: Han Wŏn-chin vs. Motoori Norinaga. Issue 1 (2nd January 2016) - Park, Hong-Kyu; Hur, Nam-Lin
ABSTRACT: The eighteenth century was a peaceful era for East Asia, ruled by the emperors of Ching. However, intellectuals who refused to accept the Great Ching order appeared in Chosŏn and Japan. They developed homeland-centric ideologies. This article compares the Han Wŏn-chin (韓元震, 1682–1751)'s Chosŏn-centrism with the Motoori Norinaga (本居宣長, 1730–1801)'s Japan-centrism. There is a lot of research about the Norinaga's Japan-centrism in Japanese academia, which contains both aspects of the culture theory and order theory. In Korea, however, discourse about Chosŏn-centrism is still ongoing argument under the concept of 'Chosŏn's Sino-centrism (朝鮮中華主義)'. I would like to pay attention to that, although homeland-centrism is constructed with two aspects, which are theories of international order and culture, the Chosŏn's Sino-Centrism related discourse only discuss about culture theory aspect. Therefore, comparing Japan-centrism, which contains both culture and order parts, I will point out the problem of Chosŏn's Sino-centrism discourse has, and assert that when Han Wŏn-chin came up with the idea of a Chosŏn-led world, Chosŏn-centrism had born with both aspects of culture and order. In order to reveal the Chosŏn-centrism, I will use a new concept called 'Zhonghua Community (中華共同體)'.